Epidemiology of Meningococcal Disease, New York City, 1989–2000 - Alexandre Sampaio Moura; Ariel Pablos-Méndez; Marcelle Layton; Don Weiss (Emerging Infectious Diseases, 2003)
Study of the epidemiologic trends in meningococcal disease is important in understanding infection dynamics and developing timely and appropriate public health interventions. We studied surveillance data from the New York City Department of Health and Mental Hygiene, which showed that during 1989–2000 a decrease occurred in both the proportion of patients with serogroup B infection (from 28% to 13% of reported cases; p<0.01) and the rate of serogroup B infection (from 0.25/100,000 to 0.08/100,000; p<0.01). We also noted an increased proportion (from 3% to 39%; p<0.01) and rate of serogroup Y infection (from 0.02/100,000 to 0.23/100,000; p<0.01). Median patient age increased (from 15 to 30 years; p<0.01). The case-fatality rate for the period was 17%. As more effective meningococcal vaccines become available, recommendations for their use in nonepidemic settings should consider current epidemiologic trends, particularly changes in age and serogroup distribution of meningococcal infections.